Synthesis of (R)-2, 2’- (1, 1’-binapthyl-2, 2’-diylbis (oxy) bis (N-9, 10-dioxo-9, 10, -dihydroanthracen-2-yl) acetamide) as Fluorescent Sensor for Amino Acids - Chuenka, Apinya; Songsasen , Apisit; Wannalerse, Boontana (Agriculture and Natural Resources, 2015)
A new fluorescent sensor, (R)-2, 2’- (1, 1’-binaphthyl-2, 2’-diylbis (oxy) bis (N-(9, 10-dioxo-9, 10, -dihydroanthracen-2-yl) acetamide), L1 was synthesized and characterized by 1H and 13C nuclear magnetic resonance (NMR), Electrospray ionization mass spectroscopy (ESI-MS) and elemental analysis (EA). L1 exhibits significant fluorescence quench in the presence of various amino acids (D-Ala, L-Ala, D-Leu, L-Leu, D-Phe, L-Phe D-Trp and L-Trp) at concentrations of 5 × 10-5 M. From fluorescence titration studies, D-Trp is able to clearly decrease the fluorescence intensity of L1, when compared to other amino acids. The association constant, of L1 and D-Trp is 1.26 × 103 M-1 using a Benesi-Hildebrand plot. Job analysis shows that L1 forms a complex with D-Trp in a 1: 1 fashion. A highly selective response of L1 is useful for the selective fluorescence recognition of D-Trp. In addition, upon addition of D-Trp to the deuterated dimethyl sulfoxide solution of L1, a considerable shift of the signal of NH protons was found in the 1H nuclear magnetic resonance (NMR) spectrum. Moreover, the aromatic region was found to shift upfield. Therefore, the receptor L1 selectively recognized D-Trp over other amino acids. The complexation of L1 and D-Trp is formed via the hydrogen bonding and π-π stacking interactions.